The frequency of poly(G) tracts in the human genome and their use as a sensor of DNA damage. (February 2015) - Murray, Vincent
Graphical abstract: Highlights: The frequency of occurrence of poly(G) sequences was determined in the updated human genome. There was an exponential increase in the frequency of poly(G) sequences for lengths above eight nucleotides. Could poly(G) sequences be a sensitive sensor of cellular DNA damage? Abstract: Tandem repeats of short DNA sequences are commonly found in human DNA. These simple sequence repeats or microsatellites are highly polymorphic in the human genome. Since the anti-tumour agent cisplatin preferentially forms DNA adducts at runs of consecutive guanine nucleotides (poly(G)), the position and frequency of occurrence of poly(G) sequences in the updated human genome was investigated. There are more runs of consecutive guanines than would be expected by random chance. This especially true for poly(G) sequences longer than approximately n = 9. A plot of poly(G) length against log(observed/expected) frequency produced a straight line for n > 9. A similar observation was also found for poly(A) DNA sequence repeats. This data implied that the increase in observed/expected frequency is directly related to length of DNA repeat. It was proposed that long runs of consecutive guanine nucleotides could be a sensitive sensor of cellular DNA damage since a number of DNA damaging agents cause lesions at poly(G) sequences.